2020
DOI: 10.1128/jb.00159-20
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa PA14 Enhances the Efficacy of Norfloxacin against Staphylococcus aureus Newman Biofilms

Abstract: The thick mucus within the airways of individuals with cystic fibrosis (CF) promotes frequent respiratory infections that are often polymicrobial. Pseudomonas aeruginosa and Staphylococcus aureus are two of the most prevalent pathogens that cause CF pulmonary infections, and both are among the most common etiologic agents of chronic wound infections. Furthermore, the ability of P. aeruginosa and S. aureus Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 62 publications
(47 reference statements)
2
28
0
Order By: Relevance
“…Inoculation of the layered model containing TSB medium with both bacterial species did not result in stable coexistence of both bacterial species, as S. aureus did not reach bacterial numbers of even 10 5 CFU/ml, while P. aeruginosa CFU/ml was unaffected by coculturing with S. aureus (Figure 4). These findings are in concordance with studies that have shown P. aeruginosa to produce antimicrobial exoproducts effective against S. aureus 24,32–34 …”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Inoculation of the layered model containing TSB medium with both bacterial species did not result in stable coexistence of both bacterial species, as S. aureus did not reach bacterial numbers of even 10 5 CFU/ml, while P. aeruginosa CFU/ml was unaffected by coculturing with S. aureus (Figure 4). These findings are in concordance with studies that have shown P. aeruginosa to produce antimicrobial exoproducts effective against S. aureus 24,32–34 …”
Section: Resultssupporting
confidence: 92%
“…These findings are in concordance with studies that have shown P. aeruginosa to produce antimicrobial exoproducts effective against S. aureus . 24 , 32 , 33 , 34 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While direct contact between bacterial cells was presumed to mediate this effect, other studies identified P. aeruginosa secreted products affecting the resistance of S. aureus to antimicrobial compounds. In particular, secondary metabolites from the 4-hydroxy-2-alkylquinolines (HAQ) family such as HQNO increase the resistance of S. aureus to aminoglycosides notably through the induction of the SCV phenotype i ( Hoffman et al, 2006 ; Mitchell et al, 2010 ; DeLeon et al, 2014 ; Orazi and O’Toole, 2017 ; Orazi et al, 2019 , 2020 ). Interestingly, late P. aeruginosa isolates from CF infections often lack HQNO production but are still able to protect S. aureus from tobramycin.…”
Section: Coexistence Promotes Cooperative Behaviors Between mentioning
confidence: 99%
“…Treating A. fumigatus cultures with supernatants from PAO1 grown in Romling ASM and SCFM2 would likely lead to different results. The P. aeruginosa AQ HQNO is known to alter S. aureus susceptibility to antibiotics (96). Therefore, differential production of HQNO by P. aeruginosa in different ASM could affect the results of antibiotic susceptibility assays performed in different ASM formulations.…”
Section: Resultsmentioning
confidence: 99%